Monitoramento e controle de ambiente para cultivo de hortaliças em uma estufa - Rosa, Gabriela Bertolini Ferreira (2023)
Aiming to provide ideal conditions for the healthy and productive growth of plants, the This paper presents the study and development of the project of a monitoring system ramento and control for a greenhouse in a home environment, used in the cultivation of certain species of vegetables, since they are harmed by some external factors that are not within the suitable for its growth, such as temperature, humidity, luminosity, among others. Initially, a bibliographic review is carried out on the main concepts related to vegetable greenhouses, as well as on the environmental variables they affect the development of plants. In addition, monitoring techniques and control currently used in this context. Thus, from the Arduino hardware, it is proposed a monitoring system based on strategically distributed sensors inside the greenhouse. These sensors are capable of capturing real-time data and transmitting it for the microcontroller, enabling appropriate decision-making. The next step It consists of the development of an automated control system. Finally, they are conducted experiments in a real greenhouse, with the aim of evaluating the efficiency and feasibility of the Proposed system. The results obtained are analyzed and compared with the conditions of conventional cultivation. It is verified that the proposed monitoring and control system is able to significantly improve the environment of vegetable greenhouses, providing a healthier growth and increasing crop yields.